Ocean acidification may be increasing the intensity of lightning over the oceans - Asfur, Mustafa (Sci Rep, 2020)
The anthropogenic increase in atmospheric CO(2) is not only considered to drive global warming, but also ocean acidification. Previous studies have shown that acidification will affect many aspects of biogenic carbon uptake and release in the surface water of the oceans. In this report we present a potential novel impact of acidification on the flash intensity of lightning discharged into the oceans. Our experimental results show that a decrease in ocean pH corresponding to the predicted increase in atmospheric CO(2) according to the IPCC RCP 8.5 worst case emission scenario, may increase the intensity of lightning discharged into seawater by approximately 30 ± 7% by the end of the twenty-first century relative to 2000.